2014
DOI: 10.1111/1095-9270.12058
|View full text |Cite
|
Sign up to set email alerts
|

Morgawr: an experimental Bronze Age-type sewn-plank craft based on the Ferriby boats

Abstract: This paper reports on the construction of a full-scale Bronze Age-type sewn-plank boat based on the Ferriby boats. The boat, which was named Morgawr, was constructed in the National Maritime Museum Cornwall in Falmouth, England, during 2012 and the first months of 2013, as part of a larger exhibition in the museum. This paper provides the background and context of the project, describes the process of building the craft, and reflects in particular on differences between Morgawr and the 'hypothetical reconstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…These vessels broadly date to the late 2nd and 1st millennium BC and were stitched through rounded holes. Cleats were also used to reinforce the integrity of the hull (Van de Noort et al ., : 297–301). However, the sewn‐plank boat tradition of northwest Europe was not limited to the shores of the British Isles.…”
Section: Geographical and Chronological Scopementioning
confidence: 99%
See 1 more Smart Citation
“…These vessels broadly date to the late 2nd and 1st millennium BC and were stitched through rounded holes. Cleats were also used to reinforce the integrity of the hull (Van de Noort et al ., : 297–301). However, the sewn‐plank boat tradition of northwest Europe was not limited to the shores of the British Isles.…”
Section: Geographical and Chronological Scopementioning
confidence: 99%
“…There have been considerable efforts to understand vessels held together with fibres in Northern Europe, in particular in the United Kingdom, where two reconstructions of the vessels discovered in North Ferriby, Ferriby 1 (1880–1680 cal BC), Ferriby 2 (1940–1720 cal BC), and Ferriby 3 (2030–1780 cal BC) (Wright, ), have been built, Oakleaf and Morgawr (Gifford and Gifford, ; Gifford et al ., ; Van de Noort et al ., ), as well as a half‐scale model named Ole Crumlin‐Pedersen , based on the remains of Bronze Age ‘Dover Boat’ found and excavated in Dover, England (Darrah, , ; Crumlin‐Pedersen, ). However, all of these vessels are held together with individual yew withy stitches, rather than continuous stitching, so are not discussed in any depth here.…”
Section: Experimental Reconstructionmentioning
confidence: 99%
“…No surviving evidence for any Bronze Age boat at Salcombe site has been found. It can only be assumed that either contemporary sewn plank vessels such as found at Ferriby, northeast England (Wright et al, 2001;Van de Noort et al, 2014) or Dover, southeast England (Clark, 2004), or log boats as found at Carpow, southeast Scotland (Strachan, 2010) were involved in transporting the objects recovered. The locations of the departure and destination are unknown with the debate complicated by the high probability that two temporally distinct Bronze Age shipwrecks can be identified at Salcombe.…”
Section: Importance Of the Salcombe Copper Ingotsmentioning
confidence: 99%
“…The relevance of prehistoric woodworking skills in the socio-cultural evolution has been stated by other archaeological studies as well. The investigation of ancient wooden houses (Coles, 2006) and the experimental construction of a Bronze-Age-type sewn-plank boat (Van de Noort et al, 2014) have also proved the particular know-how of the first carpenters. The recovering and understanding of these forgotten skills is a challenging research task as the early human life can only be analysed by tangible evidences and an intangible heritage must be connected, in whatever form it takes, to the present (Stefano et al, 2012).…”
Section: Introductionmentioning
confidence: 99%